Modelling the Effects of Snail Control and Health Education in Clonorchiasis Infection in Foshan, China - Shujing Gao; Ruixia Yuan; Yujiang Liu; Xinzhu Meng (Complexity)
Clonorchiasis is the most important food-borne parasitic disease in China. In this paper, a mathematical model of clonorchiasis sinensis is proposed to mimic its transmission dynamics to assess the effects of intervention strategies such as snail control, health education, and chemotherapy. A threshold dynamics in terms of the basic reproductive number R0 has been established; that is, if R0<1, the disease dies out and the disease-free periodic solution is globally asymptotically stable, and if R0>1, then the disease breaks out. The effects of different control measures are compared by numerical simulations. The numerical results suggest that it is necessary to strengthen health education and improve faeces management and illustrate that snail control is the most effective way to be implemented in the clonorchiasis sinensis control in Foshan.